Capturing the benefits of Ecosystem Services to guide Decision-making in the Greater Virungas Landscape of the Albertine Rift Region - Kasangaki, A.; Kanyamibwa, S.; Burgess, N.D.; Nasero, N.; Asasira, J.; Maritim, Z. (University of Cambridge and WWF-US, 2012)
The Greater Virunga Landscape (GVL) is a biodiversity rich area located within the Albertine Rift and hosts several protected areas. The high human population within the GVL depends to some extent on goods and services derived these protected areas. These ecosystem goods and services include water, non timber forest products such as fuelwood, medicinal plants and handicraft materials, honey, and bush meat. The landscape also serves regulatory functions such as water purification, carbon sequestration, and climate moderation. With support from the MarcArthur Foundation, The University of Cambridge in partnership with the Albertine Rift Conservation Society and WWF US, implemented a three year project to map and quantify ecosystem services within the GVL, with the aim of providing information on the status of ecosystem services and how these will likely change under different development scenarios in the future. The information generated aims to guide decision makers on how to manage these ecosystem services and work towards improving the livelihood of communities within the GVL.
Keywords: ecosystem; Greater Virungas Landscape; communities